Curcumin vs Chloroquine in Coronavirus Global Pandemic: Trend analysis Study in Google - Maslichah Mafruchati (Institute of Medico-legal Publications Pvt Ltd, 2020)
COVID-19 is an infectious disease caused by the newly discovered corona virus. Curcumin and Chloroquineare one of the medications to combat against the pandemic. This paper has objective to analyze the trendsinside the use of Chloroquine and Curcumin as medical treatment against corona in global big data. Thisstudy uses quantitative method of data mining design in collecting the data. This study uses simple randomsampling to determine the number of the population needed for this study. This study uses Google trendsto gather the statistical result based on the keyword. The result shows that curcumin is more popular tobe searched as information in bigdata. USA is the country with the biggest demand of information aboutcurcumin, as seen on the number of queries variation as well as the relevance score. It can be concluded thatinformation about curcumin has demanded more because of low side effect than chloroquine.